2020
DOI: 10.2147/ndt.s241984
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with the Development of Postnatal Depression After Cesarean Delivery: A Prospective Study</p>

Abstract: Pre-operative association factors (pain and psychological vulnerability) could significantly contribute to post-Cesarean pain; however, limited information is available on the development of postnatal depression (PND). We aimed to investigate the development of PND and its association with pain vulnerability and psychological vulnerability factors. Patients and Methods: Women undergoing Cesarean delivery under spinal anesthesia were given pre-operative questionnaires, psychological and pain assessments includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
(43 reference statements)
0
17
0
1
Order By: Relevance
“…Correspondingly, data have shown that early skin-to-skin contact in the operation room reduces pain [18]. The fear of pain and anxiety regarding upcoming surgery are associated with an increased risk of early postnatal depression after CD [29]. Notably, women reported feeling significantly less exhausted during CCB compared to during CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, data have shown that early skin-to-skin contact in the operation room reduces pain [18]. The fear of pain and anxiety regarding upcoming surgery are associated with an increased risk of early postnatal depression after CD [29]. Notably, women reported feeling significantly less exhausted during CCB compared to during CCS.…”
Section: Discussionmentioning
confidence: 99%
“…e transmission of pain signals from periphery to central sensitization is a dynamic process [31]. Pain signals could be amplified by the transmission of nociceptive information (hyperalgesia), suppressed (analgesia), or relayed unaltered [32]. Pain modulation occurred in the dorsal horn of the spinal cord, where peripheral nerves relay sensory information to the brain through projection neurons [33].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative factors, for instance pain and anxiety, could significantly contribute to postcesarean delivery pain and other poor outcomes, including postoperative psychological vulnerability and postpartum depression. 15 , 16 It is well-known that up to 20% of new mothers can develop postpartum depression during the first year after giving birth. 17 The resulting increased risks of suicide ideation, infanticide, as well as childhood and adolescent developmental and behavioral problems make this a serious public health issue.…”
Section: Erector Spine Plane (Esp) Blockmentioning
confidence: 99%